Mutation and Diversity of Diphtheria Toxin in Corynebacterium ulcerans - Otsuji, Ken (Emerg Infect Dis, 2019)
Corynebacterium ulcerans infection is emerging in humans. We conducted phylogenetic analyses of C. ulcerans and C. diptheriae, which revealed diverse diphtheria toxin in C. ulcerans. Diphtheria toxin diversification could decrease effectiveness of diphtheria toxoid vaccine and diphtheria antitoxin for preventing and treating illnesses caused by this bacterium.